2013
DOI: 10.1095/biolreprod.112.104844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leptin on Lipopolysaccharide-Induced Remodeling in an In Vitro Model of Human Myometrial Inflammation1

Abstract: Reorganization of myometrial extracellular matrix (ECM) is essential for the uterus to achieve powerful synchronous contractions during labor. Remodeling of the ECM has been implicated in membrane rupture and cervical ripening. Because maternal obesity is associated with both delivery disorders and elevated circulating leptin levels, this study aimed to assess the ability of leptin to interfere with lipopolysaccharide (LPS)-induced myometrial ECM remodeling. Myometrial biopsy samples were obtained from women u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
4
17
0
1
Order By: Relevance
“…Degradation of collagens has been observed in several cells and tissues after LPS challenge [42,43], and our findings of reduced cardiac fibroblast activation and collagen production after LPS are in line with these observations. Interestingly, these effects could be mediated by shed syndecan-4 ectodomains.…”
Section: Discussionsupporting
confidence: 92%
“…Degradation of collagens has been observed in several cells and tissues after LPS challenge [42,43], and our findings of reduced cardiac fibroblast activation and collagen production after LPS are in line with these observations. Interestingly, these effects could be mediated by shed syndecan-4 ectodomains.…”
Section: Discussionsupporting
confidence: 92%
“…If such a relationship is present in myometrium then it could contribute to the decreased contractility associated with hypoxia and pH [52] change. Visfatin/NAMPT is also produced in greater amounts during stretch, leading to the suggestion that this is a mechanism of increasing metabolite supply for cytoskeletal rearrangement and then for the mechanical work of labour [53]. This pathway was also shown to be important in visfatin's relaxant effects in rat and human mesenteric microvessels [54].…”
Section: Discussionmentioning
confidence: 99%
“…Obese women have been shown to have different physiological characteristics that may lead to dysbiosis of the genital tract, including high plasma estrogen levels, systemic inflammation, and low immune function (10,11). Furthermore, several previous studies showed that prepregnancy body mass index (BMI) and plasma leptin levels may influence the outcomes of pregnancies, such as preterm delivery, low-birth-weight infants, macrosomia, and delivery disorders (12,13). These obstetric and neonatal disorders were also associated with Lactobacillus inersdominant microbiota in early pregnancy and the presence of bacteria related to bacterial vaginosis, as detected by vaginal smears (8,(14)(15)(16).…”
mentioning
confidence: 99%